Neonatal pyruvate dehydrogenase deficiency due to a R302H mutation in the PDHA1 gene: MRI findings - Soares-Fernandes, JP (2012)
Pyruvate dehydrogenase (PDH) deficiency is one of the most common causes of congenital lactic acidosis. Correlations between the genetic defect and neuroimaging findings are lacking. We present conventional and diffusion-weighted MRI findings in a 7-day-old male neonate with PDH deficiency due to a mosaicism for the R302H mutation in the PDHA1 gene. Corpus callosum dysgenesis, widespread increased diffusion in the white matter, and bilateral subependymal cysts were the main features. Although confirmation of PDH deficiency depends on specialized biochemical analyses, neonatal MRI plays a role in evaluating the pattern and extent of brain damage, and potentially in early diagnosis and clinical decision making.